Factors influencing organizational citizenship behaviour (OCB) among local government employees in Lagos State, Nigeria - Amaka, Ikenna Jennifer; Alias, Siti Noormi; Mohd Anuar, Mohd Ashraff (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Organizational Citizenship Behaviour (OCB) is known to be one of the most important concepts in organizational effectiveness. Determining how OCB contributes to an organization through the organization’s social system has been of increasing interest to both scholars and managers. Although the factors influencing organizational citizenship behaviours have been widely investigated by researchers, there is little research interest on organizational citizenship behaviour in public organization, especially in developing countries. This study examined the factors influencing organizational citizenship behaviour among employees of local government areas in Lagos State, Nigeria. The study employed multi-stage sampling techniques on 400 employees of three selected local government areas in Lagos using self-administered questionnaire. The data collected was analysed using SPSS version 23.0. The result of the study indicated that there was high level of employee job satisfaction, organizational commitment, organizational justice, employee engagement as well as OCBs. The result of the multiple regression indicated that Job satisfaction has the most significant influence on organizational citizenship behaviour with positive coefficient weight value of 0.414 (p<0.001). The Organizational commitment is the second most important variable influencing OCB with coefficient weight value of 0.320, (p<0.001). More so, employee engagement was statistically significant (p<0.001), with positive coefficient weight of 0.298. The organizational justice has the least influence on OCB in the model with a coefficient weight value of 0.222, and statistically significant (p<.001). Based on the outcome of this study, it can be concluded that job satisfaction, organizational commitment, organizational justice and employee engagement have positive and significant influence on OCB. It is therefore recommended that the local government authorities, human resources professionals and policy makers need to understand the significant determinants of OCB and focus on these variables in order to design sound people-oriented policies and strategies that would improve OCB among their employees for the overall organizational performance.